Hyoid Bone Position in Orthodontic Patients (Orthodontic Journal of Nepal, 2019)
Introduction: Hyoid bone is attached to mandible and cranium by different ligaments and muscular attachments and plays important role in maintaining of functions of oral cavity such as posture of tongue. Hyoid bone is attached to mandible and cranium by different ligaments and muscular attachments and plays important role in maintaining of functions of oral cavity such as posture of tongue.Materials & Method: Study was carried out in Nishtar Institute of Dentistry, Multan in May-June 2019. Lateral cephalogram of 113 patients were taken from orthodontic department and drawn by using 3H pencil and acetate matte sheets. Skeletal malocclusions were distributed into Class I, Class II and Class III on the bases of ANB angle. Hyoid bone position was determined using method devised by Bibby and Preston. IBM SPSS was used to assess the statistical data and mean, correlations and one sample t-test were applied.Result: Data shows that in population of Multan, Pakistan, hyoid bone is posterior and downward in position and lies close to mandibular plane. Mean value of C3-H, Hyoid angle and H-RGn was 28.76mm ± 4.01mm, 15.26º ± 5.85º and 33.6mm ± 6.12mm.Conclusion: It is concluded that hyoid bone is positioned more downward and backward direction in Skeletal Class I cases from given sample, moderately in Class III and less in Class II cases.